Poverty, Fertility Preferences and Family Planning Practice in the Philippines - Aniceto C. Orbeta (Philippine Institute for Development Studies (PIDS), 2005)
This paper looks at the interaction of poverty, fertility preferences and family planning practice in the Philippines using the series of nationally representative Family Planning Surveys conducted annually since 1999 augmented by census and other survey data. Its contribution lies on providing recent and nationally representative empirical evidence on the long running but largely unresolved debate in the country on the relationship between fertility preferences and family planning and socioeconomic status. A detailed characterization of the relationships was done using cross tabulation analyses. In addition, and more importantly, a recursive qualitative response model was estimated to identify the determinants of fertility preferences and family planning practice across socioeconomic groupings. The paper show that while the number of children ever born is indeed larger among poorer households, their demand for additional children is lower and their contraceptive practice poorer. This result indicates that, in the case of the Philippines, the larger number of children among the poor is more the result of poorer contraceptive practice rather than higher demand.
Keywords: 330; family planning; Philippines; fertility preferences; socioeconomic status; Armut; Armutsbekämpfung; Familienplanung; Philippinen